ANALISIS TINGKAT KESEHATAN BANKALTIMTARA PERIODE 2012 - 2016 - -, Sahrul Hamdani (EKONOMIA, 2019)
Analysis of Bankaltimtara Health Level for the 2012-2016 period at PT Bank East Kalimantan and North Kalimantan, Samarinda (under the guidance of Mr. Robin Jonathan as supervisor I and Mrs. Ida Rahmawati as supervisor II). The purpose of this study was to determine and analyze the soundness of Bankaltimtara in the period 2012-2016 which was assessed by the CAMEL method, namely to find out and analyze Bankaltimtara Financial Performance in the period 2012-2016 from CAR (Capital Adequacy Ratio), KAP (Earning Assets Quality) , NPM (Net Profit Margin), ROA (Return On Assets), BOPO (Operating Expenses versus Operating Income) and LDR (Loan to Deposit Ratio). The basic theory used in this study is Horne & Wachowicz Jr. (2012: 2) argues that the notion of financial management is: "Financial management is related to the acquisition of assets, funding, and asset management based on several general objectives". CAMEL Analysis in accordance with Bank Indonesia regulations Number 6/10 / PBI / 2004 dated April 12, 2004 concerning the rating system for Commercial Banks (State Gazette of the Republic of Indonesia number 38 in 2004, addition to State institutions Number 4382). The analytical tool used in this study is to use the CAMEL method with the following analytical tools: CAR (Capital Adequacy Ratio), KAP (Earning Asset Quality), NPM (Net Profit Margin), ROA (Retrun On Asset), BOPO (Operating Expenses to Operating Income), LDR (Loan to Deposit Ratio). The results showed that Bankaltimtara's health level in the 2012-2016 period was analyzed based on the ratio of CAR, KAP, NPM, ROA, BOPO and LDR. CAR ratio for the period of 2012 - 2016 in a healthy predicate according to Bank Indonesia standards CAR > 8%. The ratio of KAP for the period of 2012 - 2016 in a healthy predicate according to Bank Indonesia standard KAP < 6%. The NPM ratio for the period of 2012-2016 was in an unhealthy predicate according to Bank Indonesia standards > 66%. ROA ratio for the 2012-2016 period in a healthy predicate according to Bank Indonesia standards ROA > 0.5%. BOPO ratio for the 2012-2016 period in a healthy predicate according to Bank Indonesia BOPO standard < 96%. The LDR ratio for the 2012-2014 period was in a healthy predicate according to the Bank Indonesia LDR < 100% standard and the 2015-2016 period in an unhealthy predicate according to the Bank Indonesia LDR > 100% standard